The Role of Storytelling Methods Using Hand Puppets in Early Children’s Language Development - Mujahidah, Nurul; Damayanti, Eka; Afiif, Ahmad (Universitas Nahdlatul Ulama Surabaya, 2021)
Using hand puppets in a storytelling activity (which can resemble human or animal forms) as a learning medium has many beneficial. This study aims to determine the role of the hand puppet storytelling method in early childhood language development. This research uses a library research type, Systematic Literature Review (SLR), namely the study of various scientific studies relevant to research to obtain inferences in the form of new findings that can later be replicated. The data source used is secondary data, which has been previously published in the form of books, journals, and previous studies. The data collection technique in this research is documentation. The data analysis technique uses content analysis, a research technique for making inferences that can be replicated. The results showed that storytelling using hand puppet media played a role in developing children’s language. The role of the storytelling method using hand puppet media in early childhood language development, namely (1) encouraging children to be more skilled at speaking; (2) make children more interested and more active in listening; (3) increasing children’s self-confidence; (4) improve children’s listening skills; (5) developing receptive language skills of children; (6) developing children’s early literacy; (7) enabling children to retell stories that they’ve been heard; (8) add word recognition and vocabulary to children’s language; and (9) developing children’s oral language skills. This research has implications for learning, especially for teachers to use various media and appropriate learning methods according to the child’s learning type. Children become interested and more enthusiastic in participating in the learning process.